Detailed Analysis of Crystal Structure and Optical Properties of Green Synthesized Nanoparticles: Application for Photocatalyst Degradation of Methylene Blue - Selestin, Arul Vathana; Karuppiah, Amudhavalli; Thanapalan, Vinoline Golda; Christopher, Infant Francita Fonseka (Trends in Sciences, 2022)
We report the green chemistry reduction approach method for the synthesis of Manganese Oxide nanoparticles (MnO NPs), Copper Oxide nanoparticles (CuO NPs) and Manganese-doped Copper Oxide nanoparticles (Mn-doped CuO Nps). Aqueous extract from the seeds was used as reducing and capping agents. The detailed crystal structure analysis was investigated; crystallite size, crystallinity, morphological index, x-ray density, bulk density, specific surface area, porosity, Lorentz factor, Lorentz polarization factor and other parameters were calculated. Simple EDX mapping reveals the presence of Mn, Cu, O and C. FTIR analysis was used to determine the bond length of a nanocomposite. In the visible area, nanoparticles have higher optical absorption, with bandgaps varying from 1.79 (MnO), 2.18 eV (CuO) and 1.72 eV (Mn-doped CuO). After 90 min, the photodegradation rate of Mn-doped CuO nanocatalysts was 93.73 % while using a smaller amount of catalyst (0.1 g) at pH 7. The pseudo-first-order MB photocatalytic decomposition kinetic model has a high correlation coefficient value (R2 > 0.95). It was found that Mn-doped CuO NPs have higher photocatalytic efficiency and can be used as potential photocatalysts for industrial dye degradation. HIGHLIGHTS Green synthesis of Mn, Cu, and Mn-doped Cu nanoparticles by Bambusa seeds extract Characterized via XRD (crystal structure), UV-Vis Diffuse Reflectance spectra (UV-DRS), FT-IR (bond length), and FESEM-EDS analysis Photocatalytic degradation of organic methylene blue dye using Mn-doped CuO nanoparticles GRAPHICAL ABSTRACT